TRADISI MAMPADUOI DALAM PERJANJIAN BAGI HASIL SAWAH DI NAGARI GUNUNG MEDAN - Irawan, Vendra (Fakultas Syariah, 2018)
The aim of this research is to understand and analyze the practice of mampaduoi system in profit sharing agreement of rice field in Nagari Gunung Medan, West Sumatera, based on the study of Islamic Law and the Act Number 2 Year 1960 regarding Profit Sharing Agreement. This is an empirical research with sociological juridical approach. The result of analysis shows that mampaduoi system in profit sharing agreement done in Nagari Gunung Medan is a kind of cooperation which employs kinship principle (badunsanak) and mutual help. The ratio is 4 (1:3) for close family members and 3 (1:2) for non family. Islam figures and chief of tribal in Nagari Gunung Medan consider mampaduoi system is in accordance with Islamic sharia as what has been determined by Jumhur Ulama regarding mukhabarah agreement. However, based on the act Number 2 Year 1960, the system is not appropriate because it is not legally written.